HERMENEUTIK GANDA FAZLUR RAHMAN: KONSEP DOUBEL MOVEMENT DALAM TAFSIR AL-QURAN KONTEMPORER - Salahuddin Harahap; Raudatul Husna; Rahma Rizki Nasution; Adil Arwana Sipayung (Wahdatul Ulum Institute, 2026)
This study aims to examine Fazlur Rahman's double movement theory, a contemporary approach to Qur'anic interpretation involving two movements: the first, which begins with a contemporary perspective, leading to the time when the Qur'an was revealed, and the second, which returns to the present. In general, this movement combines inductive and deductive reasoning. This study uses a qualitative analysis method using Fazlur Rahman's double movement theory and library research, examining various relevant literature sources. The results of this study indicate that Fazlur Rahman's double movement hermeneutic has proven effective in dynamizing contemporary Qur'anic interpretation by distilling eternal moral principles from historical context and adaptively applying them to modern issues such as qisas (religious retaliation), social ethics, and equality, thus producing a relevant, systematic understanding, avoiding classical literalism, and strengthening the relevance of Islam in the global era.